Customary land tenure and registration in Australia and Papua New Guinea : anthropological perspectives - Weiner, James F.; Glaskin, Katie (Asia-Pacific environment monograph, 2007)
Anthropologists fifty years ago would probably have regarded a collaborative presentation of essays on indigenous land tenure in Australia and Papua New Guinea (PNG) as a dubious undertaking, if not a category error. Aboriginal and Melanesian systems were functionally distinct, one adapted to the needs of a hunting and gathering economy, the other to sedentary horticulture. Going back another fifty years, such a conjunction would have been intelligible only if its purpose was to exhibit lower and higher stages in cultural evolution. As the authors of the present volume are not motivated by a desire either to overturn functionalism or advance evolutionism, what brings them together in common cause?